Fabrication of Poly(o-Chloroaniline) to MMT Clay as Potential Flame-Resistant Material - Iqbal, Shahid; Nadeem, Sohail; Ahmad, Mirza Nadeem; Javed, Mohsin; Alsaab, Hashem O.; Awwad, Nasser S.; Ibrahium, Hala A.; Elkaeed, Eslam B.; Alshammari, Fwzah H.; Alwadai, Norah; Alahmdi, Mohammed Issa; Bahadur, Ali; et al. (Frontiers in Materials, 2022)
Polyorthochloroaniline (POC) nanocomposites with montmorillonite (MMT) Clay (POC/MMT clay NCs) (POC/MMT) clay nanocomposites among organic/inorganic nanocomposites are the most widespread and attractive due to their distinctive properties in addition to inexpensive, abundance, and attractive characteristics like ion-exchange and great surface area properties and have ample applications. The preparation of Polyorthochloroaniline nanocomposites with montmorillonite (POC/MMT) clay nanocomposite has been completed chemically with the help of oxidative polymerization of orthochloroaniline in the presence of montmorillonite (MMT) Clay. POC will be admixed with montmorillonite (MMT) clay at various concentrations, by keeping the o-chloroaniline monomer in the reaction mixture constant. The load percentage of MMT clay in the nanocomposites had changed to explore the effect of MMT clay on the properties of POC. The characterization and properties have been determined by using different techniques. FTIR spectroscopy was used to investigate the interactions between the POC and MMT. The complete homogeneous dispersion of MMT Clay in POC matrix was examined by scanning electron microscope (SEM) analysis that revealed the compactness. The thermal stability of polymer-clay nanocomposites was determined by thermogravimetric analysis (TGA). The results of DSC/TGA measurements revealed that the flame retardancy and thermal stability of POC/MMT clay nanocomposites were considerably improved.